Metaethics after Moore. - Horgan, Terry (Oxford University Press, UK, 2006)
This substantial collection of sixteen original papers is one of a number of publishing ventures to have recently marked the centenary of the publication of G.E. Moore's Principia Ethica. It is not primarily a historical enterprise. Evidently what the editors have encouraged contributors to provide are cutting edge contributions to contemporary metaethics that engage with Moorean themes and concerns in ways that make the continuing relevance of those themes manifest. And this, to. an impressive extent, is precisely what most of them have delivered. ... This is a rewarding collection of pape.